ANALYZING STUDENTS’ ABILITY IN WRITING OFFICIAL LETTERS AT GRADE V SD BABUSSALAM PEKANBARU - Ika Krisma Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The results of research found that writing official letters was divided into complete and incomplete based on thirteen parts, namely the head, date, number, attachment, subject, objectives, greetings, opening paragraphs, content, closing remarks, concluding paragraph, the letter delivery, and language. Based on these results, the highest percentage was showed in the appendices of the letter in which 81.94% of the students could write the appendix well. Meanwhile, the lowest percentage was achieved on the date with a percentage of 25%. 19 students obtained very high grades (>90) with a percentage of 26.38%. Thus, writing an official letter was included as an ability and skill in writing since writing a good official letter needs a comprehensive attention to the systematics in writing an official letter. Knowledge, skills and abilities in systematic writing should be taken into account because students would be categorized as uncapable to write an official letter without this understanding.